MARKSHADING AND GEODESIC MONITORING OF SAFE CONDITION OF TAIL DUMP DAMS - Sayyidkosimov S.S.; Rakhimova M.Kh; Khakberdiev M.R (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Analysis and generalization of the experience in the construction and operation of tailings dams of concentrating factories shows that at the present stage of development of the mining industry, one of the aspects of the problem is the task of organizing a comprehensive monitoring of alluvial enclosing structures for the entire period of their construction and operation. The essence of this article is to use the results of mine surveying and geodesic instrumental observations of deformation processes occurring in the body of dams and on the surface of tailing dumps slopes to assess and predict their stability.